Analisis Pengaruh Komitmen Afektif dan Presepsi Kepemimpinan yang Positif terhadap Organizational Citizenship Behavior Melalui Motivasi Intrinsik sebagai Variabel Intervening: - Yogananda Enggara Putra Hana (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to analyze the relationship between Affective Commitment and Positive Leadership Perceptions of Organizational Citizenship Behavior Through Intrinsic Motivation as an Intervening Variable at BALAI BESAR KERAJINAN BATIK KOTA YOGYAKARTA. This research method uses descriptive quantitative using primary data obtained from distributing questionnaires. In this study using simple random sampling technique, namely the sample is taken at simple random and each member of the sample has the same opportunity to be sampled. The number of samples taken in this study were 78 questionnaires. Data were analyzed using SPSS and Smart PLS. The results showed that affective commitment had a positive and significant effect on intrinsic motivation with a significance level of 0.003 <0.05, so hypothesis I was accepted. Perceptions of positive leadership have a positive and significant effect on intrinsic motivation with a significance level of 0.003 <0.05, so hypothesis II is accepted. Affective commitment has no positive and significant effect on OCB with a significance level of 0.407 > 0.05, so hypothesis III is rejected. Perceptions of positive leadership have a positive and significant effect on OCB with a significance level of 0.00 <0.05, so hypothesis IV is accepted. Intrinsic motivation has a positive and significant effect on OCB with a significance level of 0.0014 <0.05 (p<0.05) so hypothesis V is accepted. Affective commitment to OCB with intrinsic motivation as an intervening variable with a significance level of 0.003 <0.05 (p<0.05) then hypothesis VI is accepted. Positive leadership perception of OCB with intrinsic motivation as an intervening variable with a significance level of 0.000 <0.05 (p<0.05) then hypothesis VII is accepted. Keywords: Affective Commitment, Perception of positive leadership, Organizational Citizenship Behavior (OCB), Intrinsic Motivation